ANALISA ASPEK REPRODUKSI IKAN TOMAN (Channa micropeltes) DI SUNGAI BELIDA KABUPATEN MUARA ENIM - Danang Yonarta; Yulisman Yulisman; Riswandi Riswandi (Universitas Sriwijaya, 2020)
Management of snakehead fish resources in swamp waters need to be done to anticipate a decline in stock in the waters. At this time the area where snakehead fish still have an abundant population is in southern sumatera, precisely in the Belida River, Muara Enim Regency. Until now there has been no information regarding the reproductive aspects of snakehead fish, their location and spawning season. The purpose of this study was to obtain information about the reproductive aspect of snakehead fish which includes sex ratio, gonad maturity level. Gonad maturity index and egg fecundity. The research was conducted in September-December 2019. The location was determined based on the natural conditions of the Belida River and human activities. Fish sampels were caught using experimental gill nets with ½ mash net size. Sampling of fish is done every 4 months with a time interval of once a month. The resuls of study in the male and female fish ratio 1,6:1. This ratio consisted of 109 fish (62,3%) and 66 female fish (37,7%). Gonadal maturity indeks for male snakehead fish ranged from 0,21 to 0,86, while female snakehead fish ranged from 1,18 to 2,30. snakehead fish egg fecundity were 24.786 eggs with a diameter of 2,20 – 2,51